The hidden power : late cistophoric production and the organization of the provincia Asia (128-89 B.C.) - Carbone, Lucia Francesca (American Numismatic Society, 2019)
"Can the study of a local coinage provide elements useful for a better understanding of Roman provincial economic policy as a whole? Using the production patterns of the Asian cistophorus as a case study, this book aims to prove such a connection and, at the same time, hopes to provide useful tools for better understanding Roman economic policy in the province of Asia between its establishment in the 120s BC and the beginning of the Mithridatic Wars"--